2017
DOI: 10.1080/16070658.2017.1322823
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a nutrition education programme on feeding practices of caregivers with children aged 3 to 5 years in rural Limpopo Province, South Africa

Abstract: To determine the impact of nutrition education on feeding practices of caregivers with children aged 3 to 5 years at baseline and post intervention. Methodology: A pre-test-post-test control group design was chosen using eight villages (four villages in the experimental group (E) and four villages in the control group (C)). The nutrition education intervention programme (NEIP) comprised ten topics emphasising healthy eating, hygiene and sanitation. Results: Majority of children in both the experimental and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…A intervention graded medium quality that delivered behaviour change communication and unconditional cash transfers to mothers in Togo improved household food security (61) . Interventions graded medium quality that included nutrition education and cooking demonstrations increased diet diversity scores of women and children in Ethiopia (42) and South Africa (88, 89) . These interventions were deemed medium quality due to the self-reported measures.…”
Section: Resultsmentioning
confidence: 99%
“…A intervention graded medium quality that delivered behaviour change communication and unconditional cash transfers to mothers in Togo improved household food security (61) . Interventions graded medium quality that included nutrition education and cooking demonstrations increased diet diversity scores of women and children in Ethiopia (42) and South Africa (88, 89) . These interventions were deemed medium quality due to the self-reported measures.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have found beliefs about the health benefits of food have a larger influence on consumption than the quality of foods (Rakotosamimanana et al, 2014), and misconceptions about the health value of foods are common (Farris et al, 2019). However, many Malagasy are interested in education on diet diversity and health (Asgary et al, 2015;Farris et al, 2019), and education has been shown to positively influence dietary behavior (Mushaphi et al, 2017). Effective strategies to encourage diet diversity in limited-resource countries have been previously identified and include: comprehensive community-based health education, focusing on types of foods and incorporating familiar foods, incorporating caregivers into education, individualized nutrition counseling, and a combination of communication approaches with repeated reinforcement (Khan et al, 2013;Mushaphi, et al, 2017;Sanchez, 2005;Sethi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, several universities (such as University of Venda, University of the Free State and Stellenbosch University) in South Africa are jointly implementing Nutrition Education Intervention Programmes (NEIPs) that encourage the consumption of indigenous foods, and some positive indicators in consumption are already showing. A study carried out by Mushaphi et al (2017), in Limpopo Province indicates that consumption of a number of indigenous vegetables increased considerably after the implementation of the NEIP. There was a significant increase in the percentage of children who consumed indigenous vegetables such as black jack (Bidens pilosa; [8.2%; 37.6%]), spider flower (Cleome gynandra; [6.5%; 34.3%]) and wild-jute plant (Corchorus hirstirus or Corchorus olitorius; [9.1%; 37.5%]) at 95% CI for the percentage difference between baseline and post-intervention (Mushaphi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A study carried out by Mushaphi et al (2017), in Limpopo Province indicates that consumption of a number of indigenous vegetables increased considerably after the implementation of the NEIP. There was a significant increase in the percentage of children who consumed indigenous vegetables such as black jack (Bidens pilosa; [8.2%; 37.6%]), spider flower (Cleome gynandra; [6.5%; 34.3%]) and wild-jute plant (Corchorus hirstirus or Corchorus olitorius; [9.1%; 37.5%]) at 95% CI for the percentage difference between baseline and post-intervention (Mushaphi et al, 2017). The increase in consumption necessitates an increase in supply through cultivation, or else there will be increased pressure on wild species possibly leading to extinction of such species (Maseko et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation